2001
DOI: 10.1088/0305-4470/34/28/102
|View full text |Cite
|
Sign up to set email alerts
|

Supersymmetry and the spontaneous breakdown of 𝒫𝒯 symmetry

Abstract: The appearances of complex eigenvalues in the spectra of PT -symmetric quantummechanical systems are usually associated with a spontaneous breaking of PT . In this letter we discuss a family of models for which this phenomenon is also linked with an explicit breaking of supersymmetry. Exact level-crossings are located, and connections with N -fold supersymmetry and quasi-exact solvability in certain special cases are pointed out.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
382
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(392 citation statements)
references
References 26 publications
10
382
0
Order By: Relevance
“…The first complete proof of spectral reality and positivity for H in (2) was given by Dorey et al in Ref. [27,28].…”
Section: P T Quantum Mechanicsmentioning
confidence: 99%
“…The first complete proof of spectral reality and positivity for H in (2) was given by Dorey et al in Ref. [27,28].…”
Section: P T Quantum Mechanicsmentioning
confidence: 99%
“…Firstly, our study [2] revealed that the manifest non-Hermiticity of the models of the type (1) leads to the reliable leading order approximation only after we select our harmonic oscillator approximant as lying very far from the real axis (i.e., from the Hermitian regime). Such a recipe is, apparently, deeply incompatible with a smooth modification of the traditional zero-order approximants occurring in current Hermitian 1/ℓ recipes (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Within this class, the strong-coupling version of DDT oscillators (1) with α ≫ 1 forms a particularly suitable testing ground as it combines the necessary reality of its spectrum with the smallness of the inverse quantity 1/ℓ. Moreover, the phenomenologically appealing non-Hermitian models like (1) are rarely solvable in closed form so that the presence of a "universal" small parameter 1/ℓ ≪ 1 offers one of not too many ways towards their systematic approximate solution.…”
Section: Introductionmentioning
confidence: 99%
“…When ≥ 0, the PT symmetry is unbroken, but when < 0, the PT symmetry is broken ( figure 1). Moreover, some extensions of non-Hermitian PT -symmetric Hamiltonians H given by equation (2.1) have also been considered [15][16][17][18][19][20]. The notion of pseudo-Hermiticity has also been introduced [21][22][23][24] and it has been shown that every Hamiltonian with a real spectrum is pseudo-Hermitian [25].…”
Section: Non-hermitian Pt -Symmetric Hamiltoniansmentioning
confidence: 99%